Mediating role of social capital on the association between negative life events and quality of life among adults in China: A population-based study - Zhang, Jianghui; Wang, Songmei; Zhang, Xuehui; Han, Xiaoyu; Deng, Haoyuan; Cheng, Nan; Sun, Yunrui; Song, Chongwei; Hou, Zhongxin; Yin, Jianzhong; Meng, Qiong (Frontiers in Public Health, 2022)
Objective To evaluate whether social capital played a mediating role in the relationship between negative life events (NLE) and quality of life (QoL) among adults in China after proposed a conceptual model based on stress buffering theory. Methods A cross-sectional study was conducted based on baseline survey from the Chinese Multi-ethnic Cohort (CMEC) in Yunnan province. A total of 22,866 adults were recruited by multistage stratified cluster sampling. A structured questionnaire was used to collect the general demographic characteristics and the occurrence of NLE. A self-developed brief social capital scale was utilized to assess the social capital and the EQ-5D-5L scale was used to measure the QoL. The relationships among NLE, social capital and QoL were analyzed using multiple linear regression analyses. Structural equation models were used to evaluate whether social capital had a mediating effect on the relationship between NLE and QoL. The standardize coefficient (β) and it's 95% confidence intervals (CI) were calculated in this process. Results The mean age of participants was 52.70 years old. The mean of EQ-5D index value was 0.92 (SD = 0.12) and the mean of EQ-VAS score was 71.77 (SD = 13.80). NLE not only directly affected EQ-5D index value [β = −0.127, 95% CI (−0.144, −0.110)] but also indirectly negatively affected EQ-5D index value through social capital [β = −0.019, 95% CI (−0.023, −0.015)]. Social capital had a direct positive effect on EQ-5D index value [β = 0.114, 95% CI (0.097, 0.133)]. A similar pattern was identified for the association between NLE and EQ-VAS score. The direct effect of NLE on EQ-VAS score was negatively significant [β = −0.132, 95% CI (−0.146, −0.118)]. Moreover, the indirect effect through social capital was also negatively significant [β = −0.022, 95% CI (−0.026, −0.019)]. There was a positive direct effect of social capital on EQ-VAS score [β = 0.135, 95% CI (0.117, 0.151)]. Conclusion Social capital played an important mediating role in the relationship between NLE and QoL, and it alleviated the negative effects of NLE on the QoL of the community residents in China. Providing reliable social capital for community residents experiencing NLE could effectively improve their quality of life.